Financial Literacy and Inclusion Analysis of the Community of Pulau Seribu (A Case Study on Pramuka Island on the Limitations of Banking Financial Services in the Pulau Seribu) - Erni Prasetiyani; Ai Nety Sumidartini; Achmad Barlian (Ilomata International Journal of Tax and Accounting, 2021)
: The progress of a region can be measured by the level of financial literacy of its population and financial inclusion. DKI Jakarta is in the top financial ranking for literacy and inclusion, but it is inversely proportional to the Pulau Seribu region. This research is a qualitative research with the technique of obtaining data through in-depth interviews with residents in the Pulau Seribu. The results are processed with a Strength Weakness Opportunity Threat (SWOT) analysis to produce a map of the strengths, weaknesses, opportunities and threats that exist in the Pulau Seribu region. With the SWOT condition in the region, it is hoped that the policy makers, namely the Otoritas Jasa Keuangan (OJK), the DKI Jakarta Regional Government and the community themselves are able to synergize in formulating strategies to accelerate the backwardness of the Pulau Seribu with DKI Jakarta.